Faith and Social Character Education of Sociological Education Perspective: an Implementation of Classroom Management in Islamic School - Subiyantoro, Subiyantoro (Prodi Manajemen Pendidikan Islam FITK UIN Sunan Kalijaga Yogyakarta, 2017)
process of learning Core Competence I (faith dimension) and Core Competence II (social dimension), channeled through school culture in sociology dimension using Looking Glass Self theory from Cooley and Three Self Elements theory from Freud. Research and Development method is employed to reveal: characteristic of faith and social dimensions in the students of State Islamic School (MAN) Wates 1in indirect instruction; which effective education model should be applied in the students’ faith and social character education. The measurement before and after treatment is conducted using observation and in-depth interview methods towards teachers and students with students’ faith and social characteristic measurement scale instrument. The analysis uses data reduction, data display, and verification. The result shows thatin a learning faith and social character educationportrait, teachers find it difficult to relate material and skill being taught with faith and social character education being ddeveloped. The in-class education model proposed includes inculcating, facilitating, modeling, and skill developing. The increase of character motivates teachers to improve their competence in buiding faith and social dimensions of the students.